Association between eHealth literacy and health outcomes in German athletes using the GR-eHEALS questionnaire: a validation and outcome study - Geiger, S.; Esser, A. J.; Marsall, M.; Muehlbauer, T.; Skoda, E.-M.; Teufel, M.; Bäuerle, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Athletes face various sports-related stressors, which may increase their risk for physical and mental health symptoms. With the internet as an important source of (health) information, it is important for athletes to have eHealth literacy, i.e. the ability to access, understand and use electronic health information and services. However, it is presently uncertain whether eHealth literacy of athletes is linked to better health outcomes such as reduced injury frequency and behaviours like decreased substance abuse.